The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1063/1.3682301
|View full text |Cite
|
Sign up to set email alerts
|

Mixed self-assembled monolayer of molecules with dipolar and acceptor character—Influence on hysteresis and threshold voltage in organic thin-film transistors

Abstract: Study of Nb epitaxial growth on Cu(111) at sub-monolayer level J. Appl. Phys. 112, 074328 (2012) Increased efficiency of light-emitting diodes incorporating anodes functionalized with fluorinated azobenzene monolayers and a green-emitting polyfluorene derivative APL: Org. Electron. Photonics 5, 230 (2012) Increased efficiency of light-emitting diodes incorporating anodes functionalized with fluorinated azobenzene monolayers and a green-emitting polyfluorene derivative Appl. Phys. Lett. 101, 153306 (2012)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…This results in considerable hysteresis in the voltage-current char-acteristics of the device. 13 When analyzing semiempirical molecular orbital calculations on such SAMs, 14 we noticed that the local electron affinity 15,16 indicated electron traps in the interstitial volumes between adjacent fullerenes in the semiconductor layer and that these traps were particularly deep when three fullerenes were involved. 14 A literature survey revealed that several groups have studied covalently linked fullerenes, their radical anions and dianions, [17][18][19][20][21][22][23][24][25][26][27][28][29][30] but that little attention has been paid to non-bonded van der Waals aggregates of fullerenes.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…This results in considerable hysteresis in the voltage-current char-acteristics of the device. 13 When analyzing semiempirical molecular orbital calculations on such SAMs, 14 we noticed that the local electron affinity 15,16 indicated electron traps in the interstitial volumes between adjacent fullerenes in the semiconductor layer and that these traps were particularly deep when three fullerenes were involved. 14 A literature survey revealed that several groups have studied covalently linked fullerenes, their radical anions and dianions, [17][18][19][20][21][22][23][24][25][26][27][28][29][30] but that little attention has been paid to non-bonded van der Waals aggregates of fullerenes.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…Mixing different molecules with different diploes were a common method in the fabrication of memory devices as it combines the advantages of the two materials. Jedaa et al [62] reported a memory device based on three selfassembled materials with different functional groups: C 18 -PA, F 15 C 18 -PA, and C 60 -terminated octadecyl phosphonic acid on Al 2 O 3 substrate. Mixing these self-assembled molecules could effectively adjust the threshold voltage and hysteresis characteristics of the memory device.…”
Section: Surface Diploesmentioning
confidence: 99%
“…When enough negative bias voltage was applied in the gate electrode, the holes could be generated and the threshold voltage would be shifted to the negative direction. Jedaa et al [62] reported that mixing two or more kinds of self-assembly materials could effectively regulate the threshold voltage, suggesting that self-assembly technology was important to improve the performances of memory device. In 2010, Burkhardt et al [86] designed two self-assembly molecules: n-octadecylphosphonic acid and C 60 -derivative compound Reproduced with permission.…”
Section: Sam-aumentioning
confidence: 99%
See 1 more Smart Citation
“…While such methodology is useful for obtaining an overall picture of the graphene doping environment it makes it difficult to understand the exact relationship between SAMs and graphene. SAMs are commonly used in organic field‐effect transistors to modify the work function of metal electrodes, quench charge trap sites at the interface between semiconductor and metal or dielectric, and modulate the position of the threshold voltage . SAMs represent an ideal platform for control of graphene electronics as they can be designed and functionalized at the molecular scale to cater to specific device requirements.…”
Section: Introductionmentioning
confidence: 99%